Pursuing quality of life : from the affluent society to the consumer society - Nevarez, Leonard (Routledge, 2011)
From anxieties over work-life balance and entangling technologies, to celebrations of cool jobs and great places to live, quality of life frames the ways we enhance our lives and legitimate social change today. But how does the idea of quality of life envision the greater good, and what gets lost as a result? This book provides the critical framework for understanding the idea's contexts and tensions that are conspicuously missing in popular discussions, professional activities, and scholarly research on quality of life. With multiple case studies taken across North America and Europe, it provides a sociological perspective on the contradictory ways we talk about and pursue quality of life in relation to technology, consumerism, family, work, public space, rural ways of life, and ultimately the final years of life. Drawing on contemporary and classical social theory, it provides an incisive account of the historical shifts in developed societies over the last half-century that have transformed our views and pursuits of quality of life. Originally a promise to undertake collective effort and pursue social justice at a moment of unprecedented opportunity, quality of life now enshrines a solipsistic ideal with which to accommodate the storms of market forces and political failure. -- Product Description.